Fuelwood consumption and supply strategies in mangrove forests - Insights from RAMSAR sites in Benin - ADANGUIDI, JEAN; PADONOU, Elie Antoine; ZANNOU, A. S. AFIO; Houngbo, Sidol B.E.; SALIOU, Idelphonse; AGBAHOUNGBA, Symphorien (My University, 2020)
In West Africa, fuelwood is the main source of energy in rural areas. The growing needs for wood energy cause the degradation of forests, including mangroves in Benin. This study assessed the wood energy needs in the mangrove areas of RAMSAR sites 1017 and 1018 in Benin. Surveys were conducted with 614 stakeholders (firewood housekeepers, collectors and sellers, manufacturers and sellers of charcoal, and food sellers). The annual wood consumption, annual wood consumption per capita, annual wood need per capita, and the projection of future wood needs per year and over 10 years were estimated using appropriate formulas. The results showed that, on average, 8.21 m3 of firewood and 23.19 kg of charcoal were consumed per capita per year. Annual firewood and charcoal needs were 12.83 m3 and 36.25 kg per capita, respectively. A gap of around 36% remains to be filled to meet wood energy needs at RAMSAR sites 1017 and 1018 in Benin. The wood needs are projected to be 18.859806 hm3 for firewood and 53,271.485 tons for charcoal in 2027. Sustainable strategies including the use of domestic gas and solar energy should therefore be developed to meet these wood energy needs and to save mangrove ecosystems.
Keywords: Mangroves; wood energy; consumption; RAMSAR; Benin